Researching the Margins
XVI, 208 p.
Keywords: Social researchers are increasingly aware of their obligations to the 'hard to reach' communities they research. This book identifies the issues associated with researching these communities and offers both conceptual analyses and practical suggestions. The contributors are members of ARCSHS staff or drawn from the affected communities themselves.